Effect of infection by the protistan parasite Marteilia refringens on the enzyme activity and energy reserves of oyster Ostrea stentina (Payraudeau, 1826) in Tunisia - Elgharsalli, Refka; Seguineau, Catherine; Arzul, Isabelle; Aloui-Béjaoui, Nejla; Quere, Claudie; Moal, Jeanne (Journal of the Marine Biological Association of the United Kingdom, 2018)
WOS:000430473000014 International audience This is the first study of the metabolic enzyme activity and energy state of the dwarf oyster Ostrea stentina (Payraudeau, 1826) in Tunisia and in the Mediterranean region. The main purpose of this study was to examine the modulation of the physiological status of the oyster O. stentina depending on the season and the presence of parasite Marteilia refringens. The prevalence of bonamiosis and marteiliosis were established by PCR. Bonamia exitiosa was detected only in 2.91% of oysters while the prevalence of M. refringens was 100% (30 Ind./30) in February and 93.93% (28 Ind./30) in March. A 42-87% mortality rate was reported during the study period. Biochemical analyses were carried out to evaluate the management of the energy resources in regard to the biochemical changes of lipids and carbohydrates. The enzyme activity of pyruvate kinase (PK), citrate synthase (CS) and cytochrome c oxidase (CCO) were measured and the mean level of enzyme activity was respectively 20.31 mU mg(-1) protein; 12.06 mU mg(-1) protein and 3.59 mU mg(-1) protein. Carbohydrate contents of O. stentina were very low all year round with an average of 15.18% in dry weight, and lipid contents remain similar (11.77% in dry weight) compared with the values reported for most other temperate bivalves. Enzyme activity significantly decreased over time (P < 0.001). The energy resources of the oyster O. stentina wherein much of the energy was devoted to reproduction seem to affect the defence system.